A review on the use of the inerter device in the structural coupling technique for adjacent building vibration control. (August 2022) - Pippi, Augusto de Souza; Avila, Suzana M.; Doz, Graciela
Abstract: Due to the large population density in big urban centers, building taller and closer buildings is necessary. The high flexibility of these buildings can lead to excessive vibration problems due to the action of earthquakes and strong winds. Furthermore, there is also the possibility of collision between them (pounding). The structural coupling technique has been extensively studied in recent decades due to its efficiency in attenuating excessive displacements and avoiding pounding between coupled structures. This method connects two or more buildings close together through control devices to attenuate the dynamic responses of both structures. Since 2002, several inerter-based control devices have been developed. Inerter is an element in which the force applied to it is proportional to the relative acceleration between its terminals. In 2017, inerter-based devices were introduced to the connected system to improve the structural coupling technique. Since then, several studies have been conducted to show the advantages of this combined use. Thus, this work illustrated the most recent and relevant developments on structural coupling, inerter devices, and their simultaneous use. So far, this proposal is quite promising, with motivating results, bringing possibilities for real applications with clear advantages about already consolidated devices.